Biogeochemistry of surface sediments in an Antarctic nearshore area affected by recent glacier retreat: Collins Harbour, King George Island - Venturini, Natalia (2020)
Biochemical composition of sedimentary organic matter, grain size, major and trace elements were analysed at 10 sampling stations in Collins Harbour, Maxwell Bay, to evaluate sources of particulate material in the seafloor. Surface sediment samples were taken with a grab, during the ANTAR XXV expedition in January 2018, onboard the BAP Carrasco from the Peruvian Navy. Coarse sediment fractions decreased, while mud content increased towards the centre of the bay. Positive correlation between mud and the biopolymeric carbon (BPC) indicated depositional conditions and organic material accumulation in the deepest central area. Proteins (PRT) predominated over other biochemical classes contributing to labile organic carbon, followed by lipids (LIP) and carbohydrates (CHO). PRT positive correlation with Ba, Ca and Al indicated that labile organic carbon inputs derived from marine primary production. Whereas, PRT positive correlation with K and Ti suggested also the influence of terrestrial supply through Collins Glacier meltwater runoff. Mn/Ti, Mn/Al and Fe/Al ratios decreased towards the centre of the bay, while the Ba/Al ratio showed the opposite trend. This distributional pattern suggested the diminish of glacial and terrigenous sedimentation towards the deepest central area of the bay, with the increment of marine particulate material deposition and accumulation. Igeo values between 0 and 1 showed unpolluted conditions in Collins Harbour for Cr, Ni, Cu, Zn, As and Pb, which concentrations may reflect background values for this area. Natural inputs from weathering, glacial runoff and marine primary production are main sources of particulate material in Collins Harbour, with none detected anthropogenic contributions.